Proceedings of the Workshop Contemporary Geometry and Related Topics :Belgrade, Yugoslavia, 15-21 May 2002 /Neda Bokan ... [et al.]. - Bokan, Neda
The workshop was organized by the Faculty of Mathematics of the Belgrade University and the Mathematical Institute of SANU (Serbian Academy of Science and Arts).